Restrictions on Hajj Pilgrimage for Indonesian Congregation from the Perspective of Sadd al-Dzari’ah - Siddiq, Achmad; Mubin, Muhammad Ufuqul; Maula, Ismatul; Meidina, Ahmad Rezy; Irsyad, Mohammad (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
The Hajj queue in Indonesia, which extends up to 25 years, necessitates clear and effective policies to mitigate this issue. One such policy is encapsulated in the Regulation of the Minister of Religious Affairs of the Republic of Indonesia No. 29/2015, which amends the earlier Regulation No. 14/2012 on the Implementation of Regular Hajj. This regulation prohibits individuals who have already performed the Hajj pilgrimage from re-registering for a period of 10 years. This research employs the Ushul Fiqh approach. Data were collected by reviewing and analyzing pertinent literature, including documents and regulations of the Minister of Religious Affairs, as well as several ushul fiqh books and other relevant sources. The study aims to examine the restriction as a means to prevent potential unrest in the community, in line with the concept of Sadd al-Dzari’ah. This restriction is intended to benefit those who have not yet performed Hajj and to safeguard the rights of others to undertake this worship, adhering to the principle of tasharruf al-imam ala al-ra'iyah manuth bi al-maslahah. The implementation of this policy is expected to exchange the efficiency and effectiveness of Hajj pilgrimage management and reduce public unrest. Therefore, it is crucial that this policy is executed clearly and effectively to maximize its benefits for the community.